Effect of Processing on Resistant Starch Formation in Food: A Review - Shrestha, Ashok Kumar (Journal of Food Science and Technology Nepal, 2009)
Resistant starch (RS) is the fraction of starch that remains undigested in small intestine in human and metabolized in large intestine that has potential to improve human health. Processing operations tend to destroy the structure of native starch granule forming retrograded starch (RS3) which is manifested by the change in conformation of starch structure such as crystallinity; thermal properties; morphology; viscosity and other physico-chemical properties. To improve the RS content in foods, it is imperative to know the effect of processing on the transformation of starch properties leading to altered enzyme resistance of native starch. This paper reviews the starch structure and effects of various processing techniques on the formation of enzyme resistant starch in foods. Key words : Resistant starch, Retrogradation; Structure; Processing Journal of Food Science & Technology Nepal Vol 4, September, 2008 Page: 1-11